E-Tilang Web Based Application for Merangin District Traffic Riders - Pratiwi, Regina Gita; Widiyanto, Max Teja Ajie Cipta (Universitas Muhammadiyah Semarang Press, 2021)
The development of the e-ticketing application starts from planning is identifying problems, the system running, user needs to designing the uml, database and GUI. Up to the coding stage and the application named Electronic Ticketing Application (E-Tilang) Against Traffic Offenders in Merangin Regency is web-based. The application focuses on recording tickets and the results of recording tickets that can be seen on the web. The system created by the author can simplify the process of counting and processing of numbers, both for the Kasatlanas party and the public in seeing the results of the selection trial because all activities are carried out online and the data is recorded in real time in the database